Development of Canva Based Digital Comics on Straight Motion Kinematics Materials For Student’s Learning Motivation Orientation - Hapsari, Aulia Nurmalinda; Risdianto, Eko; Medriati, Rosane (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2024)
This study aims to determine the development of digital comics learning media on the material of straight motion kinematics by students at 3 SMAN Bengkulu City. This research is R&D research using the ADDIE model. The instrument used in this study was an expert validation sheet consisting of 5 aspects, namely content, presentation, language, media, and learning motivation. Based on the results of the research that has been done, it is known that the quality of the development of digital comics learning media on straight motion kinematics material is categorized as very suitable for use, with all aspects found to be 87.08% and the results of students' perceptions of the development of digital comics learning media are obtained based on all aspects of 86.99% with very good category in 3 SMAN Bengkulu City. So, it can be said that developing digital comic learning media on straight-motion kinematics material to direct students' learning motivation is very feasible and very good to develop.